The Samaritan - Cross, Mason (Cross, Mason. Carter Blake thriller., 2016)
"The Samaritan" is a sadistic serial killer preying on lone female drivers whose cars have broken down-- and has been undetected for a decade. When Carter Blake shows up to volunteer his services, and proves to have an uncanny ability to predict the Samaritan's next moves, LAPD Detective Jessica Allen and her colleagues are suspicious. But as the Samaritan takes his slaughter to the next level, Blake must find a way to stop him-- even if it means bringing his own past crashing down on top of him.